Dynamic re-planning for cyber-physical situational awareness - Piskozub, M; Creese, S; Happa, J (IEEE, 2018)
Modern warfare increasingly depends on interconnected computers where cyber security plays an essential role. Events from the battlefield are reported to decision-makers verbally, in a textual format, but rarely graphically. In this paper we conduct a feasibility study of a real-time 3D simulation system that visually communicates cyber-physical data to obtain situational awareness. We identify whether such a system is plausible for the real-time planning of simulated battle scenarios, and how such a tool may help real-time decision-making. As part of this feasibility study, we investigate whether the addition of "presence" often described in VR literature helps or detracts value from such a simulation system. We hypothesise that experiencing the situation in virtual reality is beneficial for decision-makers' reaction time and quality of their decisions. Our simulation is built using Unreal Engine 4. It is then evaluated in a study involving four cyber security experts. The results indicate that the simulation is successful in the situational awareness aspect. Most users rate the regular monitor version higher than its virtual reality counterpart, stressing that while the immersion in VR is better, it is not as good in terms of controls, image quality, decision-making and comfort.